n-3 fatty acid supplementation during 4 weeks of training leads to improved anaerobic endurance capacity, but not maximal strength, speed, or power in soccer players - Gravina, L.; Brown, F. F.; Alexander, L.; Dick, J.; Bell, G.; Witard, O. C.; Galloway, S. D. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Omega-3 fatty acid (n-3 FA) supplementation could promote adaptation to soccer-specific training. We examined the impact of a 4-week period of n-3 FA supplementation during training on adaptations in 1RM knee extensor strength, 20-m sprint speed, vertical jump power, and anaerobic endurance capacity (Yo-Yo test) in competitive soccer players. Twenty six soccer players were randomly assigned to one of two groups: n-3 FA supplementation (n-3 FA; n = 13) or placebo (n = 13). Both groups performed two experimental trial days. Assessments of physical function and respiratory function were conducted pre (PRE) and post (POST) supplementation. Training session intensity, competitive games and nutritional intake were monitored during the 4-week period. No differences were observed in respiratory measurements (FEV1, FVC) between groups. No main effect of treatment was observed for 1RM knee extensor strength, explosive leg power, or 20 m sprint performance, but strength improved as a result of the training period in both groups (p < .05). Yo-Yo test distance improved with training in the n-3 FA group only (p < .01). The mean difference (95% CI) in Yo-Yo test distance completed from PRE to POST was 203 (66-340) m for n-3 FA, and 62 (-94-217) m for placebo, with a moderate effect size (Cohen`s d of 0.52). We conclude that 4 weeks of n-3 FA supplementation does not improve strength, power or speed assessments in competitive soccer players. However, the increase in anaerobic endurance capacity evident only in the n-3 FA treatment group suggests an interaction that requires further study.